Wadi: A Traditional Food of Dayak Ethnic At Central Borneo As An Effort of Food Warranty Based on The Local Wisdom - Dewi, Indah Sari; Hastuti, Utami Sri; Lestari, Umi; Suwono, Hadi (Proceeding International Conference on Global Resource Conservation, 2015)
Wadi is a sort of the local wisdom of Dayak ethnic at Central Borneo as the effort of food warranty when fish could be found easily or when othersÂ  sources of protein, i.e.meat is difficult to be found. Wadi is a fermentation food made from fish or meat processed traditionally by mixing the fish or the meat with salt and âlumuâ (fried rice without oil),Â  then preserved for several days until a special aroma and taste were formed,with salty and acid taste with strong aroma. The changes of the taste and aroma of the wadi is caused by fermentation processÂ  formed during the preservation. The effort to create the wadi as a local wisdom is need to be continued.Keywords: food warranty; local wisdom; traditional food Wadi